2010
DOI: 10.1258/phleb.2010.010053
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for chronic cerebrospinal venous insufficiency: is the procedure safe?

Abstract: The procedures appeared to be safe and well tolerated by the patients, regardless of the actual impact of the endovascular treatments for venous pathology on the clinical course of multiple sclerosis, which warrants long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 15 publications
3
79
0
1
Order By: Relevance
“…The safety of endovascular angioplasty and, to a lesser extent, stent placement has been reported in the setting of chronic cerebrospinal venous insufficiency and MS, 45 but the efficacy of treatment and the vascular pathogenesis on the basis of venous hypertension remains highly controversial. 46 The overwhelming evidence is that it is unlikely that a thickened jugular valve is responsible for this disease; and the absence of MS in patients with dural fistula, radical neck dissection, idiopathic intracranial hypertension, and other known causes of significant venous hypertension has also been noted.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of endovascular angioplasty and, to a lesser extent, stent placement has been reported in the setting of chronic cerebrospinal venous insufficiency and MS, 45 but the efficacy of treatment and the vascular pathogenesis on the basis of venous hypertension remains highly controversial. 46 The overwhelming evidence is that it is unlikely that a thickened jugular valve is responsible for this disease; and the absence of MS in patients with dural fistula, radical neck dissection, idiopathic intracranial hypertension, and other known causes of significant venous hypertension has also been noted.…”
Section: Discussionmentioning
confidence: 99%
“…5,16 More sophisticated CV categoric criteria (ranging from grade 1 to grade 4) were recently proposed. 15 Our preliminary experience with CV 25,30 indicates that proper training is needed for recognition of pathologic intraluminal anomalies indicative of CCSVI and that more sophisticated criteria for detection of these anomalies, such as time to empty contrast from veins or waisting of the balloon, need to be tested and validated. 24 In addition, CV is an invasive method that requires radiation exposure, and there are ethical concerns in applying this technique to a large group of HCs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, a condition called CCSVI was found with high frequency in patients with MS. 5 CCSVI presupposes that MS is associated with impaired venous drainage from the brain to the periphery due to venous anomalies in major extracranial neck and azygos veins. 5 Recent studies by using extra-and transcranial DS, [6][7][8][9][10] phase-contrast and contrast-enhanced MRV, [11][12][13] or CV 14,15 failed to confirm the high frequency of abnormal cerebral venous outflow in patients with MS versus HCs, as originally reported. 5 Previous CV studies in MS 5,[14][15][16] proposed that the extracranial venous anomalies are likely to be truncular venous malformations characterized by intraluminal defects (such as flaps, webs, septa, membranes, and malformed valves) or by extraluminal abnormalities represented by stenoses of the venous wall.…”
mentioning
confidence: 97%
“…Recent literature has suggested that restriction of extracranial venous drainage may be a risk factor in the development of MS. [1][2][3] Published series of treatment with angioplasty and/or stent placement have begun to emerge based on this yet unproved hypothesis. 4,5 Jugular venous pathology has also been linked with transient global amnesia 6,7 and migraines, [8][9][10][11] though this is controversial 11 and no clear etiologic link to venous pathology has been established for either disease.…”
mentioning
confidence: 99%